2022
DOI: 10.3389/fnut.2022.905839
|View full text |Cite
|
Sign up to set email alerts
|

The Gut Microbiome of Preterm Infants Treated With Aminophylline Is Closely Related to the Occurrence of Feeding Intolerance and the Weight Gain

Abstract: BackgroundAminophylline is widely used in the treatment of preterm infants, but it can cause feeding intolerance events, in which gut microbial dysbiosis may have a role. This study aims to investigate the relationship between the gut microbiome of preterm infants treated with aminophylline and the occurrence of feeding intolerance and weight gain rate.MethodsThis study included a cohort of 118 preterm infants. Survival analysis and multivariate Cox regression were used to evaluate the relationship between ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…There was some agreement among the 14 studies correlating the relative abundance of specific taxa with growth ( Figure 3 ). Five studies reported positive associations between Streptococcus and growth, 19 , 21 , 24 , 26 , 30 whereas four studies reported negative associations between Staphylococcus and growth. 19 , 21 , 22 , 24 Several taxa were positively correlated with growth in some studies and negatively correlated with growth in other studies; these included Enterobacteriaceae, Streptococcaceae, Acinetobacter , Bacteroides , Enterobacter , Enterococcus , Serratia , and Streptococcus .…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…There was some agreement among the 14 studies correlating the relative abundance of specific taxa with growth ( Figure 3 ). Five studies reported positive associations between Streptococcus and growth, 19 , 21 , 24 , 26 , 30 whereas four studies reported negative associations between Staphylococcus and growth. 19 , 21 , 22 , 24 Several taxa were positively correlated with growth in some studies and negatively correlated with growth in other studies; these included Enterobacteriaceae, Streptococcaceae, Acinetobacter , Bacteroides , Enterobacter , Enterococcus , Serratia , and Streptococcus .…”
Section: Resultsmentioning
confidence: 94%
“…Of the 12 observational studies, 10 were prospective cohort studies, 19–28 one was a nested case-control study, 29 and one was a retrospective cohort study. 30 There was geographic diversity, with five studies conducted in China, 23 , 26–29 four each in Europe 17–19 , 25 and the United States, 20–22 , 30 and one in Brazil. 24 Some studies included only extremely preterm infants (< 28 weeks gestation), whereas others included any preterm infant (< 37 weeks), resulting in a range of extremely low birth weight (< 1000 g) to low birth weight (< 2500 g).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The matched cohort was subsequently divided into a discovery cohort and a validation cohort. After comparing the alteration of gut microbiota and profiles of OTUs in the discovery cohort, we used the Wilcoxon rank sum test to determine the significant OTUs ( p < 0.05) for further analysis ( Shen et al, 2022 ). All the key OTUs needed to meet the following conditions: 1) The abundance was greater than 0.5% in at least one sample.…”
Section: Methodsmentioning
confidence: 99%